2011
DOI: 10.1557/mrs.2011.155
|View full text |Cite
|
Sign up to set email alerts
|

Advanced cathode materials for lithium-ion batteries

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…There is no other binary oxide in Figure 5 that simultaneously provides higher The most remarkable feature of transition metal oxide coatings is that in every panel of Figure 5 , they occupy the region between Al 2 O 3 /MgO, and the cluster of p-block compounds close to the center of the plot. Several 3d-block compounds, and mostly the trivalent 3d-metal oxides, exhibit HF-scavenging tendencies and capacities much closer to Al 2 O 3 than the rest of the p-or d-block compounds as shown in Figure 5 [15][16][17]21,23,24,32 ] while we could fi nd only a single study [ 89 ] regarding Y 2 O 3 . HfO 2 is a reasonable candidate from the 5d-block but its drawback is only a relatively small Ω G .…”
Section: Screening Materials To Find Promising Coating Candidatesmentioning
confidence: 81%
See 1 more Smart Citation
“…There is no other binary oxide in Figure 5 that simultaneously provides higher The most remarkable feature of transition metal oxide coatings is that in every panel of Figure 5 , they occupy the region between Al 2 O 3 /MgO, and the cluster of p-block compounds close to the center of the plot. Several 3d-block compounds, and mostly the trivalent 3d-metal oxides, exhibit HF-scavenging tendencies and capacities much closer to Al 2 O 3 than the rest of the p-or d-block compounds as shown in Figure 5 [15][16][17]21,23,24,32 ] while we could fi nd only a single study [ 89 ] regarding Y 2 O 3 . HfO 2 is a reasonable candidate from the 5d-block but its drawback is only a relatively small Ω G .…”
Section: Screening Materials To Find Promising Coating Candidatesmentioning
confidence: 81%
“…Numerous subsequent studies [15][16][17][18][19][20][21][22][23][24] have shown that Al 2 O 3 -coated cathodes exhibit improved properties. Many other coating materials have also been investigated such as phosphates, [ 15,22,[25][26][27] carbonates, [ 28 ] hydroxides, [ 29 ] oxides (such as ZnO, [15][16][17]30,31 ] ZrO 2 , [15][16][17]21,23,24,32 ] TiO 2 , [ 21,23,32,33 ] MgO, [ 17,20,[34][35][36][37] SiO 2 , [ 23,24 ] Cr 2 O 3 , [ 38 ] Nb 2 O 5 , [ 16 ] Ta 2 O 5 , [ 16 ] SnO 2 [ 20 ] and B 2 O 3 [ 21,23 ] ) and fl uorides (such as AlF 3 , [ 13,15,…”
Section: Doi: 101002/aenm201400690mentioning
confidence: 99%
“…Li-ion batteries have played a vital role in the development of current generation mobile devices, microelectronics and electric vehicles [1]. Due to the flammability of conventional electrolytes [2] [8,9], thus preventing use with metallic Li or other low potential anodes.…”
Section: Introductionmentioning
confidence: 99%
“…There are three crucial factors such as pore size, pore volume and surface area which can affect the performance and discharge capacity of the lithium air cathode. Carbon loading is another factor where the increase of carbon loading decreases the capacity [39][40][41][42] . Highest gravimetric capacity of 5813 mAh/g is reported at a current density of 0.1 mA/cm 2 and a carbon loading of 1.9 mg.…”
Section: Lithium Air Cathode Characteristicsmentioning
confidence: 99%